Analisis Perbandingan Kinerja Keuangan pada PT Mulia Boga Raya TBK dan PT Indofood Sukses Makmur TBK - Yastriana Sajun (Syntax Corporation Indonesia, 2024)
This study aims to analyze whether there are differences in the financial performance of the companies PT Mulia Boga Raya Tbk & PT Indofood Sukses Makmur Tbk during the 2021-2023 period based on liquidity ratios, solvency ratios, profitability ratios, and activity ratios. This type of research is quantitative descriptive with secondary data. The results of this research show that there are differences in the financial performance of PT Mulia Boga Raya Tbk & PT Indofood Sukses Makmur Tbk from 2021-2023. Where the liquidity ratio of PT Mulia Boga Raya Tbk from 2021-2023 is seen from the current ratio, quick ratio, and cash ratio as